Les oumanas: Le corps exécutif du ʻorf de la construction au M’Zab (Algérie) - Gueliane, Nora (Asinag | ⴰⵙⵉⵏⴰⴳ | أسيناك, 2019)
The M’Zab valley (Algeria) is known for its historic ksours which are of exceptional architectural and landscape character, a heritage that has maintained its integrity and homogeneity for centuries through the establishment of a construction ʻorf. A set of rules have been developped over time and accrued experience in the architectural design of Ksours. This ʻorf relies in its application on an institution termed the oumanas. This institution ensures its transmission, evolution and its application in the field. This paper presents this institution, its organization, its financing, and its role in the management of traditional building in the M’Zab area.
Keywords: Droit coutumier – Mzab; Urbanisme – Mzab

Les institutions coutumières au Mzab - Nacer, Baelhadj (2019)
Keywords: Droit coutumier – Mzab

النظم والقوانين العرفية بوادي مزاب في الفترة الحديثة - ناصر, بالحاج بن باحمد (الحياة, 2019)
Keywords: Droit coutumier – Mzab